The Measurement Properties and Acceptability of a New Parent–Infant Bonding Tool (‘Me and My Baby’) for Use in United Kingdom Universal Healthcare Settings: A Psychometric, Cross-Sectional Study - Bywater, Tracey; Dunn, Abigail; Endacott, Charlotte; Smith, Karen; Tiffin, Paul A.; Price, Matthew; Blower, Sarah (Frontiers in Psychology, 2022)
NICE guidelines acknowledge the importance of the parent-infant relationship for child development but highlight the need for further research to establish reliable tools for assessment, particularly for parents of children under one year. This study explores the acceptability and psychometric properties of a co-developed tool, ‘Me and My Baby’ (MaMB). Study design A cross-sectional design was applied. The MaMB was administered universally (in two sites) with mothers during routine 6–8-week Health Visitor contacts. The sample comprised 467 mothers (434 MaMB completers and 33 ‘non-completers’). Dimensionality of instrument responses were evaluated via exploratory and confirmatory ordinal factor analyses. Item response modelling was conducted via a Rasch calibration to evaluate how the tool conformed to principles of ‘fundamental measurement’. Tool acceptability was evaluated via completion rates and comparing 'completers' and 'non-completers' demographic differences on age, parity, ethnicity, and English as an additional language. Free-text comments were summarised. Data sharing agreements and data management were compliant with the General Data Protection Regulation, and University of York data management policies. Results High completion rates suggested the MaMB was acceptable. Psychometric analyses showed the response data to be an excellent fit to a unidimensional confirmatory factor analytic model. All items loaded statistically significantly and substantially (>0.4) on a single underlying factor (latent variable). The item response modelling showed that most MaMB items fitted the Rasch model. (Rasch) item reliability was high (0.94) yet the test yielded little information on each respondent, as highlighted by the relatively low ‘person separation index’ of 0.1. Conclusions and next steps MaMB reliably measures a single construct, likely to be infant bonding. However, further validation work is needed, preferably with ‘enriched population samples’ to include higher-need/risk families. The MaMB tool may benefit from reduced response categories (from four to three) and some modest item wording amendments. Following further validation and reliability appraisal the MaMB may ultimately be used with fathers/other primary caregivers and be potentially useful in research, universal health settings as part of a referral pathway, and clinical practice, to identify dyads in need of additional support/interventions.